Analytical Performance Requirements for Systems for Self-Monitoring of Blood Glucose With Focus on System Accuracy: Relevant Differences Among ISO 15197:2003, ISO 15197:2013, and Current FDA Recommendations. (30th June 2015) - Freckmann, Guido; Schmid, Christina; Baumstark, Annette; Rutschmann, Malte; Haug, Cornelia; Heinemann, Lutz
In the European Union (EU), the ISO (International Organization for Standardization) 15197 standard is applicable for the evaluation of systems for self-monitoring of blood glucose (SMBG) before the market approval. In 2013, a revised version of this standard was published. Relevant revisions in the analytical performance requirements are the inclusion of the evaluation of influence quantities, for example, hematocrit, and some changes in the testing procedures for measurement precision and system accuracy evaluation, for example, number of test strip lots. Regarding system accuracy evaluation, the most important change is the inclusion of more stringent accuracy criteria. In 2014, the Food and Drug Administration (FDA) in the United States published their own guidance document for the premarket evaluation of SMBG systems with even more stringent system accuracy criteria than stipulated by ISO 15197:2013. The establishment of strict accuracy criteria applicable for the premarket evaluation is a possible approach to further improve the measurement quality of SMBG systems. However, the system accuracy testing procedure is quite complex, and some critical aspects, for example, systematic measurement difference between the reference measurement procedure and a higher-order procedure, may potentially limit the apparent accuracy of a given system. Therefore, the implementation of a harmonized reference measurement procedure for which traceability to standards of higher order is verified through an unbroken, documented chain of calibrations is desirable. In addition, the establishment of regular and standardized post-marketing evaluations of distributed test strip lots should be considered as an approach toward an improved measurement quality of available SMBG systems.